PENYELESAIAN SENGKETA E-COMMERCE MELALUI ONLINE DISPUTE RESOLUTION - Suma, Muhammad Iqbal (Faculty of Law, Khairun University, 2024)
Technological breakthroughs have driven significant growth in the economic sector, especially in increasing electronic transactions through digital platforms. The growth of e-commerce transactions has also led to trade disputes that are detrimental to consumers. This study aims to see how aspects of consumer protection are in e-commerce transactions. This research will also analyze how the process of resolving e-commerce transaction disputes through settlement via Online Dispute Resolution (ODR). The results of the research show that the government has made efforts to protect consumers by issuing Law number 8 of 1999 concerning consumer protection. Even so, the law has not been able to guarantee consumer protection in digital transactions in e-commerce. This is because the model of transactions carried out via digital platforms is different from conventional face-to-face transactions. Therefore, it is necessary to optimize and change several aspects of the consumer protection law so that it is able to cover consumer protection in e-commerce transactions. One of the dispute resolution processes is through the Online Dispute Resolution (ODR), which is a Development of Alternative Dispute Resolution (AD). ODR enables efficient dispute resolution through a faster and cheaper process.